2010
DOI: 10.2140/jomms.2010.5.341
|View full text |Cite
|
Sign up to set email alerts
|

A consistent refinement of first-order shear deformation theory for laminated composite and sandwich plates using improved zigzag kinematics

Abstract: A refined zigzag theory is presented for laminated-composite and sandwich plates that includes the kinematics of first-order shear deformation theory as its baseline. The theory is variationally consistent and is derived from the virtual work principle. Novel piecewise-linear zigzag functions are used, providing a more realistic representation of the deformation states of transverse shear-flexible plates than other similar theories. The formulation does not enforce full continuity of the transverse shear stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 35 publications
2
158
0
1
Order By: Relevance
“…As an alternative ZZ function, the Refined Zigzag Theory (RZT) developed by Tessler, Di Sciuva and Gherlone [36][37][38][39] may be used. The kinematics of RZT are essentially those of a first-order shear deformation theory enhanced by ZZ variables ψ i (x, y) that are multiplied by piecewise continuous transverse functions φ (k)…”
Section: Mixed-variational Theoriesmentioning
confidence: 99%
“…As an alternative ZZ function, the Refined Zigzag Theory (RZT) developed by Tessler, Di Sciuva and Gherlone [36][37][38][39] may be used. The kinematics of RZT are essentially those of a first-order shear deformation theory enhanced by ZZ variables ψ i (x, y) that are multiplied by piecewise continuous transverse functions φ (k)…”
Section: Mixed-variational Theoriesmentioning
confidence: 99%
“…The beam segment is defined in the ( , ) x z Cartesian system, where x is the beam longitudinal axis and z is the thickness coordinate. The superscript k denotes quantities within the th k layer with Using the same notation as for the RZT [18,19,21,23], we propose the following displacement field for the th k layer…”
Section: -1) Displacement Fieldmentioning
confidence: 99%
“…Different works [18][19][20] have shown that beam models requiring 1 C continuity for the deflection field, such as that presented in Eq. (1), have theoretical difficulties to represent correctly the shear strain and the shear stress distributions in a clamped support where the following kinematic conditions are required…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations